Myocardial protection against reperfusion injury: The cGMP pathway - Garcia-Dorado, David; Agulló, Luis; Sartorio, Carmem Lluisa; Ruiz-Meana, Marisol (Thrombosis and Haemostasis, 2009)
Reperfusion injury may cause myocardial cell death and limit the benefit achieved by restoration of coronary artery patency in patients with acute myocardial infarction. The mechanism includes altered Ca2+ handling with cytosolic and mitochondrial Ca2+ overload, Ca2+- and ATP-dependent hypercontraction, cytoskeletal fragility, mitochondrial permeability transition and gap junction-mediated propagation of cell death, as well as alterations in non-cardiomyocyte cells, in particular platelets and endothelial cells. cGMP modulates favorably all these mechanism, mainly through PKG-mediated actions, but cGMP synthesis is altered in reperfused cardiomyocytes and endothelial cells by mechanisms that are only partially understood. Stimulation of cGMP synthesis during initial reperfusion by means of natriuretic peptides has been found protective in different animal models and in patients. Moreover, increasing evidence indicates that cGMP is an important step in signal transduction of endogenous cardioprotection. Thus, the cGMP pathway appears as a key element in the pathophysiology of myocardial ischaemiareperfusion and as a promising therapeutic target in patients with acute myocardial infarction.
Keywords: Ischaemic heart disease; platelet physiology; acute myocardial infarction